(3GdCQHYhf MOjkKG GdSjdbjIs - (3GdTQja CHi WGdH GdMSf Hf eMeO Hf egOi GdMSfj GdSjdbis
(3ChdgG (B:s
(3GdMOjK GdChd , Yf CfS Hf eGdc (B: (3bGd NWHfG QShd Gddg Udi Gddg Ydjg hSde Ydi fGbI GdLOYGA abGd CjgG GdfGS cGf GdehJ s
(3BNQgG (B:s
(3ef GdMOjK GdCQHYjf bhdg (B: (3hGdJHYI Ydi aGMPQhG eKd eG Md Hi JeJ HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3cJHJ GdYfGhjf HGdMeQIs
(3HYVg efbhW heVHhWs
(3hHYVg ZjQ eVHhWs
(3heged GdfbW CMjGfG s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdMOjK h GdeUWdMs